Työolojen kolme vuosikymmentä : työolotutkimusten tuloksia 1977-2008 - Lehto, Anna-Maija; Sutela, Hanna; Tilastokeskus (Tilastokeskus, 2008)
Yhteenveto (s. 218-219).
Keywords: työsuhde; yhdenvertaisuus; työnjohto; kiusaaminen; syrjintä; palkat; työviihtyvyys; työaika; työterveys; työsuojelu; työhyvinvointi; työolot